Preparing the next generation of health care providers: A description and comparison of nurse practitioner and medical student tuition in 2015. Issue 1 (8th December 2015) - Riley, Lydia; Litsch, Tyler; Cook, Michelle L.
Abstract: Background and purpose: The purpose of this study was twofold: to describe the average cost of nurse practitioner (NP) tuition based on degree program, program type, and geography; and to compare the cost of NP tuition to medical school tuition. Methods: A listing of all NP degree granting universities was obtained from the American Association of Colleges of Nursing during the fall of 2014, and tuition data were obtained from university websites. Medical school tuition data were obtained online during the fall of 2014 from the American Association of Medical Colleges. Average 1‐year tuition rates were calculated for NP programs and medical schools and compared across private and public institutions. Conclusions: Average 1‐year resident tuition for public university NP programs ranges between 8671 and 11, 077 based on type of program. The cost of 1‐year NP program tuition at the master's and the doctoral level is much lower than the cost of 1‐year medical school tuition at both private and public universities. Implications for practice: NPs can perform many of the same services as physicians in the primary care setting with comparable outcomes, yet the cost of educating NPs is much lower. NPs are a cost‐effective solution to the healthcare workforce shortage.